The Effectiveness of Multimedia Educative Games â€œJelajah Karir Bersama Ninaâ€ to Improve Students Understanding of Career Recognition in Elementary School (Universitas Negeri Semarang, 2018)
This study aims to improve understanding of career introduction of elementary students by using multimedia educational game media â€œJelajah Karir Bersama Ninaâ€. The experimental research method used the design of one group pre-post test with purposive sampling technique to determine the subject of the study of 5th grade students of elementary school as many as 21 people.The results of the study obtained an understanding of the career recognition of the students of 5th grade Integrated Islamic Elementary School (SDIT) Avicenna, before using the medium of guidance (pre-test) the mean value of 101.57 with SD 8.02, and an increase in the mean posttest 113.76 with SD 5.21. Parametric test results were found (t(20) = 11.412, p< 0.01), there are significant differences so it can be concluded that multimedia educational games â€œJelajah Karir Bersama Ninaâ€ effective to improve understanding of career introduction to elementary school students. This finding confirms that media are multimedia educational games â€œJelajah Karir Bersama Ninaâ€ can be applied to improve understanding of career recognition for elementary students.